When Thinking About Work Makes Employees Reach for Their Devices: A Longitudinal Autoregressive Diary Study - Clara Heissler; Marcel Kern; Sandra Ohly (Journal of Business and Psychology, 2022)
Based on the stressor-detachment model, previous research has assumed that work-related ICT use in the evening impairs psychological detachment. However, since most of the studies to date have assessed cross-sectional relationships, little is known about the actual direction of effects. In this 5-day diary study, we implemented a day-level longitudinal model to shed light on the causal relationships between work-related ICT use, detachment, and task progress ( N 0.167em=0.167em340 employees, N 0.167em=0.167em1289~day-level cases). We also investigated the role of unfinished work tasks because we assumed, based on boundary theory, that they are a driving force leading to impaired detachment and work-related ICT use in the evening. Contrary to current research consensus but in line with our expectations, we found that low psychological detachment increased work-related ICT use and task progress. We found no evidence for reversed lagged effects. These results applied both to planned and unplanned ICT use. Furthermore, our results support the notion that unfinished work tasks precede ICT use and detachment. Thus, our findings suggest that work-related ICT use should not be treated as a stressor in its own right in the stressor-detachment model. Instead, it needs to be investigated as a behavioral outcome that employees engage in when they cannot detach from work.
Keywords: 650; Detachment; Work-related technology use; ICT use; Technology; Supplemental work; Unfinished tasks; Longitudinal autoregressive model; Diary study